Cortical Bone quality among Pre-Iroquoian Populations of the Lower Great Lakes Region - Southern, Rebecca (My University, 1990)
This study was designed to distinguish environmental from population-based influences on cortical bone quality among pre-Iroquoian and Iroquoian populations of the lower Great Lakes region. Excavated human bone from a total of seven archeological sites in southern Ontario and Nw York State was studied. These skeletal samples span approximately 1500 years of prehistory in this region and represent populations subject to a range of environmental conditions which could have had an impact on cortical bone status. Single photon absorptiometry of the redius and radiographv of the second metacarpal and radius were used to obtain values for the bone mineral index (BMI) and percent cortical area (PCA) respectively. The data wre compared by age and by sex both within and between skeletal samples. Comparisons were also made to published data on modern populations. Significant differences were found between the skeletal samples as well as between the skeletal samples and modern populations. These results suggest that a combination of environmental and population- based factors influenced cortical bone quality among the pre-Iroquoian and Iroquoian populations of this geographic region. These findings may have impl1cations for an understanding of cortical bone loss among living Iroquoian populations in this area.
Keywords: Anthropology; Anthropology